PRAKTIK PEMBAGIAN HARTA WARISAN MASYARAKAT DI KELURAHAN MACANANG KECAMATAN TANETE RIATTANG BARAT - zubair, asni (Pasca Sarjana STAIN Watampone, 2014)
Division of inheritance practices in society aimed to highlight the behavior displayed when executing the division. This study intends to examine how and why the people doing the division of property inheritance. This study was conducted with a case study supported by the informant interview method to collect the necessary data. Then analyzed with the theories of Islamic inheritance law system and customary inheritance law system to translate the data into something meaningful.Â Â Â Â Â Â Â Â Â Â Â Â Â Â The results found that the division of inheritance practices in Macanang society dominated by the influence of society customary inheritance law. It is evident from the cases presented that almost entirely follows the pattern of customary inheritance law. When viewed from the determination of heirs, it generally addressed to the descendants of the heirs. There is only one case involving the heirâs husband as the heirs, as well as large parts of the heirs determined as the Islamic inheritance law. However, if seen from the values that are understood and the time of the division of property carried out are generally according to Islamic inheritance law.Â Â Â Â Â Â Â Â Â Â Â Â Â Â The reason of Macanang Muslim communities in the division of the inheritance that they do are quite diverse, namely: to avoid disputes, to clarify the ownership of property status, to completeness of data, to abstain from taking rights of others,Â to grant heirs, Â and Â as a form of worship to Allah.